The last song - Sparks, Nicholas (New York : London : Grand Central Pub., Sphere, 2009)
Seventeen year old Veronica "Ronnie" Miller's life was turned upside-down when her parents divorced and her father--a former concert pianist and teacher--moved from New York City to Wilmington, North Carolina. Three years later, she remains angry and alienated from her parents, especially her father ... until her mother decides it would be in everyone's best interest if she spent the summer in Wilmington with him. An unforgettable story of love on many levels.
Keywords: Teenage girls -- Fiction; North Carolina -- Fiction; Bildungsromans, American; Love stories, American; Bildungsromans; Love stories